American Cultural Imperialism in 1960s Japan as Seen in Haruki Murakami’s Norwegian Wood - Bhakti Satrio Nugroho (Faculty of Humanities, Universitas Jenderal Soedirman, 2020)
Haruki Murakami is mostly well-known for his many works and is considered as one of the most influential writers in Japan. One of his greatest works is a nostalgic novel Norwegian Wood which named after The Beatles song, Norwegian Wood (This Bird Has Flown) in their album Rubber Soul (1965). It becomes #1 bestselling novel in Japan. This novel resembles many aspects of “Americanization” of Japanese young adult life in the 1960s Japan which was strongly influenced by American popular culture. Many Japanese in this novel adopt Western culture which was popular in the United States. Hollywood and American music became central part of the main story in Haruki Murakami’s Norwegian Wood. By using cultural imperialism theory, this research focuses on the imposition and glorification of American culture in 1960s Japan which is celebrated as part of central storyline. American cultural imperialism can be seen in dissemination and glorification of American popular culture and American way of life (lifestyle) among Japanese young adults. Furthermore, they create many social and cultural changes. It is further helped by the post-war Japanese’s inferiority after losing to the United States in World War II. In fact, Western thoughts and beliefs are part of “American gifts” during U.S occupation which disseminate even after the end of occupation. Thus, this historical postcolonial relationship between Japan (as the colonized) and the United States (as the colonizer) massively supports “Americanization” of 1960s Japan which results a loss of identity and a cultural dependency of Japan toward the United States.